General dental practitioners' perceptions of, and attitudes towards, improving patient safety through a multidisciplinary approach to the prevention of medication-related osteonecrosis of the jaw (MRONJ): A qualitative study in the North East of England - Sturrock, A. (BMJ Publishing Group, 2022)
10.1136/bmjopen-2019-029951